THE INFLUENCE OF BRAIN STIMULATION ON SOCIAL LANGUAGE PROCESSING: A FOCUS ON THE RIGHT TEMPORO-PARIETAL JUNCTION - Disser, Peyton (My University, 2025)
The right temporoparietal junction (rTPJ) is known to support theory of mind and cognitive empathy - core processes involved in attributing mental states to others. However, its specific contribution to social-pragmatic language processing remains unclear. Nonliteral language, such as sarcasm and teasing, requires not only pragmatic inference but also the integration of social and emotional cues, perspective-taking, and mental state attribution. Prior studies implicating the rTPJ have largely relied on static or written stimuli, limiting ecological validity. In this study, participants viewed short video clips from the Relational Inference in Social Communication (RISC) database, featuring dynamic, multimodal interactions across four communicative conditions: sincerity, bluntness, sarcasm, and teasing. To assess the causal role of the rTPJ, participants completed both active and sham sessions of cathodal transcranial direct current stimulation (tDCS) in a within-subjects, counterbalanced design. While accuracy in interpreting speaker intent remained consistently high and was not affected by stimulation, cathodal tDCS to the rTPJ led to faster response times and lower friendliness ratings, particularly for blunt utterances. These results suggest that the rTPJ is not essential for correctly identifying communicative intent but plays a modulatory role in shaping the affective interpretation and timing of social-pragmatic judgments.
Keywords: irony; brain stimulation; social communication; temporoparietal junction; tDCS